Os profissionais da educação e as suas relações com a comunidade escolar: aprendizagens no processo de qualificação da escola mediado pela avaliação institucional - Mara Regina Lemes de Sordi; Menga Lüdke (EccoS – Revista Científica)
The dialogue between the professionals of education and the multiple actors involved in the public teaching network is presented as indispensable for the qualification of the school, and it is developed in a more concrete way when subsidized by evidences produced in processes of institutional participatory evaluation. It is emphasized that the evaluation of the quality of the school pedagogical project is benefited when professionals of education utilize resources of the investigation, learned during their process of formation, as strategies that qualify the perception of the school reality with the appropriate inclusion of the complementary perspectives of the various actors equally interested in the improvement of the educational project.